CONSTRUCTIONAL WASTE MANAGEMENT PRACTICES: INSIGHTS FOR LOCAL GOVERNMENT POLICY RECOMMENDATIONS - Lopez, Kenneth Oliver S.; Liwanag, John A. (International Journal of Engineering Technologies and Management Research, 2025)
This research explores the constructional waste management practices in Pangasinan, aiming to develop a policy brief that addresses key issues in construction-related waste management. The study focuses on profiling the municipalities of Pangasinan’s current construction waste management system, including the adequacy of human resources involved in constructional waste management system, and existing policies, activities, and programs influencing waste management as perceived by selected Civil Engineers in the province of Pangasinan. It also examines how constructional waste management practices are monitored and identifies the types of waste typically generated in construction projects by the local and provincial government, such as concrete debris, scraped asphalt, excavated materials, packaging waste, and fuel waste like oils. Moreover, the research assesses the level of awareness among local government personnel regarding waste management protocols and evaluates the seriousness of challenges faced in implementing effective constructional waste management strategies. The study is limited to constructional wastes and specific materials commonly encountered in road and building projects. Based on the findings, a thorough recommendation will be proposed to improve waste management practices, promote sustainable construction, and enhance policy formulation for the different local government units, including the Department of Public Works and Highways, of Pangasinan